Effect of Size Distribution on the Dust Acoustic Solitary Waves in Dusty Plasma with Two Kinds of Nonthermal Ions - Samira Sharif Moghadam; Davoud Dorranian (Advances in Materials Science and Engineering)
Effect of dust size, mass, and charge distributions on the nonlinear dust acoustic solitary waves (DASWs) in a dusty plasma including negatively charged dust particles, electrons, and nonthermal ions has been studied analytically. Dust particles masses and electrical charges are assumed to be proportional with dust size. Using reductive perturbation methods the Kadomtsev-Petviashvili (KP) equation is derived and its solitary answers are extracted. The coefficients of nonlinear term of KP equation are affected strongly by the size of dust particles when the relative size (the ratio of the largest dust radius to smallest dust radius) is smaller than 2. These coefficients are very sensitive to α, the nonthermal coefficient. According to the results, only rarefactive DASWs will generate in such dusty plasma. Width of DASW increases with increasing the relative size and nonthermal coefficient, while their amplitude decreases. The dust cyclotron frequency changes with relative size of dust particles.